Formulasi dan Uji Face Mist Anti Jerawat Ekstrak Kemangi dan Pepaya - Elmi Sariani Hasibuan; Ulma Sintia; Ira Nova Siregar (Jurnal Sains Farmasi Dan Kesehatan, 2026)
Acne vulgaris is a common skin disorder caused by several factors, one of which is infection by Propionibacterium acnes. The prolonged use of antibiotics may lead to bacterial resistance; therefore, safer natural-based alternatives are needed. Basil leaves (Ocimum basilicum L.) and papaya leaves (Carica papaya L.) contain secondary metabolites such as flavonoids, alkaloids, saponins, tannins, and essential oils that exhibit antibacterial activity. This study aimed to formulate a face mist containing a combination of basil leaf and papaya leaf extracts and to evaluate its physical quality and antibacterial activity against Propionibacterium acnes. This experimental study prepared four formulations: F0 (without extract), F1 (1 g basil leaf extract and 1 g papaya leaf extract), F2 (2 g and 2 g), and F3 (3 g and 3 g). The physical evaluations included organoleptic properties, pH, spray spreadability, and drying time. Antibacterial activity was determined using the agar diffusion method by measuring the diameter of the inhibition zone. The results showed that all formulations exhibited acceptable physical characteristics, with pH values ranging from 6.23 to 6.45, spray spreadability from 8.6 to 9.3 cm, and drying time from 3.19 to 5.14 minutes. Increasing the extract concentration tended to decrease spray spreadability and prolong the drying time. The antibacterial assay demonstrated that F3 exhibited the highest antibacterial activity with an average inhibition zone diameter of 12 mm (strong category), followed by F2 with 8 mm (moderate category) and F1 with 4 mm (weak category), while the positive control produced an inhibition zone of 15 mm. In conclusion, the combination of basil leaf and papaya leaf extracts can be successfully formulated into a face mist that meets the required physical quality standards and exhibits antibacterial activity against Propionibacterium acnes, with F3 identified as the optimum formulation.